Complex Housing, but Not Maternal Deprivation Affects Motivation to Liberate a Trapped Cage-Mate in an Operant Rat Task - Kalamari, Aikaterini; Kentrop, Jiska; Hinna Danesi, Chiara; Graat, Evelien A. M.; van IJzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.; Joëls, Marian; van der Veen, Rixt (Frontiers in Behavioral Neuroscience, 2021)
Early life environment influences the development of various aspects of social behavior, particularly during sensitive developmental periods. We studied how challenges in the early postnatal period or (early) adolescence affect pro-social behavior. To this end, we designed a lever-operated liberation task, to be able to measure motivation to liberate a trapped conspecific (by progressively increasing required lever pressing for door-opening). Liberation of the trapped rat resulted either in social contact or in liberation into a separate compartment. Additionally, a condition was tested in which both rats could freely move in two separate compartments and lever pressing resulted in social contact. When partners were not trapped, rats were more motivated to press the lever for opening the door than in either of the trapped configurations. Contrary to our expectation, the trapped configuration resulted in a reduced motivation to act. Early postnatal stress (24h maternal deprivation on postnatal day 3) did not affect behavior in the liberation task. However, rearing rats from early adolescence onwards in complex housing conditions (Marlau cages) reduced the motivation to door opening, both in the trapped and freely moving conditions, while motivation for a sucrose reward was not affected.